Anjos de açúcar “catando a poesia que entornas no chão” da escola: a poesia e a afetividade na prática pedagógica do teatro - Guimarães, Gleuter Alves (2016)
This article presents the trajectory of my Professional Master's research in Arts - Theatre (PROFARTES) at the Federal University of Uberlandia. The project was carried out in the State School Dom José Gaspar of Araxa, MG. It presents the motivations to develop a working experience with poetry and theater for high school students. The relationship of my career in education with the theater scene is described as a motto to convey the idea of art in school, where students try experiences and seek spaces for expression. I chose two activities with the students experienced during the survey to represent the work of theatrical workshops, and interpretation of poetic texts. I produced a workshop of improvisation and interpretation about the lyrics of the song "Construction" by Chico Buarque and played a construction work based on the poem "Sugar" of Ferreira Gullar. The article provides a theoretical relationship between authors who speak of poetry, theater and pedagogy focusing on experience and affectivity in practical and meaningful experiences for students in their school environment and for their lives.